Just our type: a blood donation campaign - Tan, Lynn Yanlin (Nanyang Technological University, 2023)
This paper presents Just Our Type, an integrated communication campaign aimed at increasing blood donation behaviour amongst NTU students aged 19 to 27. By raising awareness, improving attitudes, subjective norms and self-efficacy surrounding blood donation, we aim to encourage our target audience to view blood donation as a simple, yet meaningful life-saving activity that can be easily done with friends. The campaign leverages peer influence by communicating visually attractive, fresh, relatable and youth-centric content, and creating a social experience at the blood donation drive through fun group activities for friends to participate in together. To meet its objectives, the campaign utilises a mix of online and offline tactics, including a video series, an interactive exhibition and in-class presentations, and culminates in an on-campus blood donation drive organised in collaboration with the Red Cross Youth NTU Chapter. This paper covers the formative research, campaign development, execution, implementation and explores limitations and recommendations of the campaign.